Deteksi Virus Dengue pada Nyamuk Aedes aegypti (Diptera: Culicidae) yang Tersebar di Kabupaten Sumba Timur dan Sumba Barat Daya - Monika Noshirma; Ruben Wadu Willa; Muhammad Kazwaini; Arief Wibowo (Jurnal Vektor Penyakit, 2020)
Abstract Incidence Rate (IR) of Dengue fever in east and southwest Sumba district in 2015 amounted to 10.7‰ and 12.95‰ respectively. The phenomenon which is often found during this time is the transovarial transmission of the dengue virus in Ae. aegypti mosquitoes. The purpose of this research was to determine the presence of viral infections in Ae. aegypti mosquitoes through transovarial. It was a descriptive study with a cross-sectional design. The sample was an adult Ae. aegypti mosquito that is 8 to 10 days old. Dengue virus in mosquito body was checked by using immunocytochemical method Streptavidin Biotin Peroxidase Complex (ISBPC) at headsquash preparation. The resultshowed that the transovarial infection presence in male and female Ae. aegypti in East and Southwest Sumba District with Transovarial Infection Rate (TIR) in females and males ranging from 41.67%-41.92 and 25.00 – 50.00% respectively. The female and males mosquitoes TIR in East Sumba district were ranging from 20.00%-40.00% and 35.00%-40.00% respectively. East and Southwest Sumba districts are a high potential area for the transmission of dengue hemorrhagic fever with the presence of dengue virus in Ae. aegypti. Abstrak Incidence Rate (IR) Demam Berdarah Dengue di Kabupaten Sumba Barat Daya dan Kabupaten Sumba Timur pada tahun 2015 masing-masing sebesar 10,7‰ dan 12,95‰. Fenomena yang sering ditemukan selama ini adalah transmisi trans-ovari virus dengue pada nyamuk Ae. aegypti. Tujuan penelitian adalah untuk mengetahui adanya infeksi virus dengue pada nyamuk Ae. aegypti melalui trans-ovari. Penelitian ini merupakan studi deskriptif dengan desain potong lintang. Sampelnya adalah nyamuk Ae. aegypti dewasa yang telah berumur delapan sampai 10 hari. Pemeriksaan virus Dengue dalam tubuh nyamuk menggunakan metode Imunositokimia Streptavidin Biotin Peroxidase Complex (ISBPC) pada sediaan headsquash. Hasil penelitian infeksi virus dengue pada Ae. aegypti betina maupun jantan di Kabupaten Sumba Barat Daya menunjukkan adanya infeksi virus dengue melalui trans-ovari dengan Transovarial Infection Rate pada nyamuk betina berkisar antara 41,67% - 41,92, dan pada nyamuk jantan 25,00 – 50,00%. Transovarial Infection Rate di Kabupaten Sumba Timur pada nyamuk betina yang berkisar antara 20,00% - 40,00% dan pada nyamuk jantan 35,00% - 40,00%. Kesimpulannya Kabupaten Sumba Barat Daya dan kabupaten Sumba Timur merupakan daerah yang berpotensi untuk terjadinya penularan DBD dengan ditemukannya infeksi virus dengue pada nyamuk Ae. aegypti betina maupun jantan.